Balancing Requirements between the PSO and the Infrastructure Manager - Petr Nachtigall; Jan Sodoma; Jozef Gašparík (Logi)
The sustainability of rail transport is a highly debated topic. Historically, there has always been strong political support to maintain even lightly used regional lines in operation. However, the economic situation and increasing demands for rail safety have introduced new challenges, including the fundamental question of whether to continue operating a line or discontinue it. So far, no simple solution has been applied across the board. Nevertheless, there are already some Public Service Obligations (PSOs) planning for the next 10 to 15 years, putting pressure on the infrastructure manager to implement measures that guarantee a specific system travel time on the line. If these expectations are not met, they may consider shifting transport services to alternative modes of transport in the medium term. One such region facing this challenge is the Hradec Králové Region, where a thesis was developed to analyze the regional route Doudleby nad Orlicí - Rokytnice v Orlických horách. The study focuses on the technological requirements for achieving the necessary system travel time, which is also the primary goal of this paper.